Pendampingan Pembuatan Permohonan Nomor Induk Berusaha (NIB) Melalui Sistem OSS-RBA oleh UMKM - Siti Fatimah; Retno Eko Mardani; Aisyah Rukmi Widowati; Azahery Insan Kamil; Aziz Widhi Nurgoho (Nusantara Mengabdi Kepada Negeri, 2025)
After the issuance of Law Number 11 of 2020 concerning Job Creation, there are several important clusters that need to be considered, one of which is the ease of doing business which is closely related to government administration. Therefore, a system was created by the government to facilitate and legalize business actors in running their businesses in the form of a Business Identification Number (NIB). Because this NIB is a new system and is likely not widely understood by business actors, including MSMEs, it is necessary to socialize it and then provide assistance. Assistance in applying for NIB through the Online Single Submission-Risk Based Approach (OSS-RBA) System by MSMEs is an important step in managing the legality of their businesses. NIB is an identity for business actors that provides access to various facilities and legal protection. The OSS-RBA system is designed to facilitate the licensing process with a risk-based approach, where types of businesses are classified based on their risk levels. The method used in community service under this title is in the form of Socialization/Counseling and Assistance for MSMEs in submitting NIB to the OSS-RBA system. Socialization or counseling is carried out in the form of lectures and Q&A discussions so as to provide a comprehensive understanding. This assistance is carried out by academics/lecturers of the Law Study Program, Veteran Bangun Nusantara University, Sukoharjo Together with the Sukoharjo regional government, in this case represented by the Sukoharjo PMD Chamber of Commerce to ensure that MSME actors understand the procedures that must be followed and can submit NIB correctly. The assistance process includes socialization, consultation and assistance in filling in data in the OSS-RBA system. The goal is to increase the number of registered and legal MSMEs in Indonesia, so that they can access various government programs and get better legal protection.